My iPad for seniors - Rosenzweig, Gary (Que, 2013)
Covers iOS 7 for iPad Air, 3rd/4th generation, iPad 2, and iPad mini Easy, clear, readable, and focused on what you want to do. Step-by-step instructions with callouts to iPad photos that show you exactly what to do. Large, full-color, close-up photos when you run into iPad problems or limitations. Common-sense help whenever you run into problems. Tips and notes to help you get the most from your iPad. Full-color, step-by-step tasks walk you through getting and keeping your iPad working just the way you want. Learn how to: Connect your iPad to your Wi-Fi and 3G/4G LTE networks; Use Control Center to control frequently used settings; Use Siri to control your iPad or get information by speaking commands; Use iCloud to keep everything current between all your iOS devices (and even your Mac), including music, photos, emails, and more; Surf the Web, and send and receive email; Download and install apps to make your iPad even more useful; Secure your iPad; Record and edit video using iMovie for iPad; Take photos, and then edit them using iPhoto for iPad; Use AirDrop to share files and information with other iOS devices in your vicinity; Manage your contacts, and then connect with others using Messaging; Use iTunes to manage and sync iPad content with your computer; Use FaceTime and Skype to stay connected with friends and family, or to conduct video conferences; Use Pages, Numbers, and Keynote to create document, spreadsheets, and presentations.